Graphene: Controlled Synthesis of Large‐Scale, Uniform, Vertically Standing Graphene for High‐Performance Field Emitters (Adv. Mater. 2/2013). (7th January 2013) - Jiang, Lili; Yang, Tianzhong; Liu, Fei; Dong, Jing; Yao, Zhaohui; Shen, Chengmin; Deng, Shaozhi; Xu, Ningsheng; Liu, Yunqi; Gao, Hong‐Jun
<x xml:space="preserve">Abstract</x> Large‐scale, uniform, vertically standing graphene film with atomically thin edges (shown in the magnifying glass in the back cover image) is controllably synthesized using methane in a microwave‐plasma chemical vapor deposition system. This film shows excellent field‐emission properties, as demonstrated by Hong‐Jun Gao, Yunqi Liu, and co‐workers on page 250. In the lower part of the image, a plane emitter based on this vertically standing graphene film is demonstrated. The small blue spheres between the two plates represent the emitted electrons. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>